Integrated Validation System (IVS) Design for Proposal Submission of Student Activities at PPNS - Yesica Novrita Devi; Wibowo Arninputranto; Fitri Hardiyanti; M. Khoirul Hasin; Arie Indartono (Procedia of Social Sciences and Humanities, 2021)
The concept of Industry 4.0 is a combination of new technological developments that aim to facilitate human-computer interaction. Higher Education Institutions are currently not separated from the development of the industrial revolution involvement 4.0. Technology has a tremendous influence in the running of all activities of daily living, not least the performance of management in institutions of Higher Education Institutions. The demand to be able to work more effectively and efficiently in producing a product both in the form of goods and services makes PPNS have to keep up with technological developments. PPNS is expected to produce a product, both goods and services, in accordance with the expectations of the stakeholders (students, society and lecturers-employees). One of the problems that often becomes a problem is the bureaucracy that has a long flow. In this study, problems that occur in the PPNS Student Affairs Sector will be raised, namely regarding the approval of student activity proposals from the Student Association (HIMA) by the PPNS Management in Student Affairs under Deputy Director III. There are several steps that can be assisted in the process by using technology, so as to increase the effectiveness of performance in student affairs. Based on these problems and opportunities, a study is proposed with the title Integrated Validation System (IVS) Development to Optimize Student Service Performance in PPNS. With this system, it is hoped that it will help optimize the performance in the field of student affairs so that it can be more effective and efficient in serving requests for student activities at PPNS